2015
DOI: 10.1177/0734242x15574560
|View full text |Cite
|
Sign up to set email alerts
|

Co-composting of rose oil processing waste with caged layer manure and straw or sawdust: Effects of carbon source and C/N ratio on decomposition

Abstract: Rose oil is a specific essential oil that is produced mainly for the cosmetics industry in a few selected locations around the world. Rose oil production is a water distillation process from petals of Rosa damascena Mill. Since the oil content of the rose petals of this variety is between 0.3-0.4% (w/w), almost 4000 to 3000 kg of rose petals are needed to produce 1 kg of rose oil. Rose oil production is a seasonal activity and takes place during the relatively short period where the roses are blooming. As a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Ekinci et al 21 reported that the maximum decomposition existed with the initial [C/N] mix of 35.94 for composting wastes of paper‐making process with broiler litter. Onursal 37 found that the highest decomposition rate occurred with the initial [C/N] mix of 30.39 for composting agro‐industrial wastes.…”
Section: Resultsmentioning
confidence: 99%
“…Ekinci et al 21 reported that the maximum decomposition existed with the initial [C/N] mix of 35.94 for composting wastes of paper‐making process with broiler litter. Onursal 37 found that the highest decomposition rate occurred with the initial [C/N] mix of 30.39 for composting agro‐industrial wastes.…”
Section: Resultsmentioning
confidence: 99%
“…Organic matter loss (OML) were calculated from the initial, V c (0) and final V c ( θ ) organic matter contents . OML=true[(1Vc(θ)Vc(0)true)true]100 …”
Section: Methodsmentioning
confidence: 99%
“…The residual plant materials and the distillation wastewaters are the two main byproducts of oil distillation that are produced as industrial wastes [28]. The rose petals from each farm were combined with water in a weight-to-volume ratio of 1:10 to extract the oil [29]. Following the extraction process, the solid distillation wastes (SDW) from each farm were collected as triplicates.…”
Section: Plant Samplingmentioning
confidence: 99%